Physical And Chemical Characterization Of Iron Ore From East Coast Of Peninsular Malaysia - Azmi, Latifah Suha (Universiti Sains Malaysia, 2018)
This study aims to physically and chemically characterize the iron ore from Bukit Besi, Terengganu and Yan, Kedah. The particle size distribution analysis is determined by using mechanical sieve shaker. Mineralogical characterization including optical microscope and scanning electron microscope (SEM) with an energy dispersive X-ray (EDX) studies were employed to determine the ore morphology and mineral liberation. X-ray fluorescence (XRF) and X-ray diffraction (XRD) were used to identify the elemental composition and mineral phases present respectively. The volumetric analysis is used to determine the percent of Fe content in the samples. The particle size distribution for both samples are in the range of coarse grained soil which is sand. The major element present based on the XRF result is Fe with 67% and the three highest minor element present are titanium, zinc and arsenic. Based on the XRD pattern, the dominant phases present are goethite, hematite and quartz. Hematite, quartz and sulphide are minerals that observed under optical microscope and the percentage of mineral liberation for sample A is 70% while for sample B is 68%. The percent of Fe content in the sample A is 39.45% and for sample B is 40.28%. The information gathered from this characterization study will aid in the selection of suitable ore extraction process.